Men, gender and violence against women - Lima, Daniel Costa; Büchele, Fátima; Clímaco, Danilo de Assis (Saúde e Sociedade, 2008)
Considering the commitment made by the Brazilian Government to restrain and prevent violence against women, signed in various international conferences, and in view of the promulgation of the Law 11.340/06 - Lei Maria da Penha -, this article intends to develop a reflection on the incorporation of men and of the gender perspective in efforts to prevent and attend to violence against women. Despite the increasing interest of scientific literature and health intervention in the involvement of men, especially in the field of sexual and reproductive rights, comparatively, reflections and interventions directed at men who have committed violence against women have received far less attention from governmental and non-governmental institutions, and from the academy. The article presents some concepts and data on violence against women and provides an overview of the connection between gender, health and masculinities; it analyzes some studies that approach the subject of men and violence against women and shares some experiences carried out with men to prevent this form of violence; finally, it offers some final thoughts on the subject.